Organizational Change & Restructuring: Analisis Bibliometrik & Literature Review pada Basis Data Scopus (1987–2021) - Jajang Ginanjar; Sam'un Jaja Raharja; Rivani Rivani (Universitas Winaya Mukti, 2023)
Change is essential for organizations in sustainable growth and especially in a highly competitive business environment. The literature on the concepts of organizational change and restructuring is important in an effort to provide a reference for academics in exploring scientific developments as well as being useful for practitioners in providing options regarding the application of these concepts in the field. This study aims to provide an overview of the past, current and future research directions from the research field of Organizational Change & Restructuring, namely to see and provide links or relationships between the fields of organizational change and restructuring through bibliometric analysis. The method used in this study is a combination of quantitative and qualitative by mapping the relationship between Organizational Change and Restructuring research using a two-step research approach: 1) Bibliometric technique to analyze 263 publications by presenting publication distribution data, mapping visualization & network density, and keyword analysis. 2) Furthermore, based on document citation data, analyze the 12 articles that occupy the top number of citations. For further review of the literature, comparing with research findings before or after according to the theme of each article. The results of the study indicate that there is still a lot of room for exploitation and exploration of the combined study of Organizational Change and Restructuring, so it is hoped that by taking the two analytical steps above, it will eventually provide some kind of recommendation for future research.